Análise ambiental da substituição do processo de pré-tratamento de superficie com banho de fosfato de zinco por nanocerâmico em uma empresa metalmecânica - Centenaro, Francine (2015)
A literature review was conducted to identify the advantages and disadvantages on environmental issues in the case of zinc phosphate bath, as well as for the alternative proposal of nanocerâmico bath. The study was conducted in a metal-mechanic sector industry located in northwestern Rio Grande do Sul Etate in order to verify the possibility of modification of the pretreatment of metal parts process to be painted in order to minimize the environmental aspects of form of waste without interfering with the quality of the parts. The pretreatment is essential step in the manufacturing process of items and metal clusters that have finished painting, because it removes the dirt which cause corrosion and improves the adhesion of the ink. The results were satisfactory, since the adhesion test can be seen that the process change will not affect the quality of the items. In a table, you can present the advantages and disadvantages of both methods of treatment, with regard to several aspects. Even having a higher initial cost, the change of the phosphate bath process by nanocerâmico, it becomes advantageous because it reduces bulk and facilitates the treatment of the effluent generated by reducing the presence of toxic metals, thus adopting a conduit less environmentally intrusive.